Exploring Healthcare Workers’ Readiness And Acceptance Of Electronic Medical Record Implementation - Dwii Novriansyah; Fani Oktafianti; Wiwik Anggi; Khusnul Khotimah; Novia Endjlina; Khairunnisyah Khairunnisyah; Fitriah Fitriah (Universitas Dehasen Bengkulu, 2026)
This study aims to explore healthcare workers’ readiness and acceptance toward the implementation of Electronic Medical Records (EMR) using a qualitative approach. A descriptive exploratory design was employed to gain an in-depth understanding of healthcare workers’ experiences and perceptions. Data were collected through semi-structured in-depth interviews with healthcare workers, including doctors, nurses, and medical record staff, selected using purposive sampling. The data were analyzed using thematic analysis. The findings revealed that healthcare workers generally have positive perceptions of EMR, particularly in improving efficiency, data accuracy, and quality of healthcare services. However, variations in acceptance and readiness were identified, influenced by factors such as perceived usefulness, perceived ease of use, organizational support, and individual technological readiness. Several challenges were also found, including limited training, technical issues, and inadequate infrastructure. The results are interpreted using the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and Technology Readiness Index (TRI), which provide a comprehensive understanding of factors influencing EMR implementation. This study highlights the importance of system usability, organizational support, and continuous training in enhancing healthcare workers’ readiness and acceptance. Strengthening these aspects is essential to ensure effective and sustainable EMR implementation in healthcare settings.